Designing and Explaining the Convergence-Based Financial Services Marketing Model in Tehran Stock Exchange (Mixed Approach) - Mirzahasan Hosseini; Neda Bashiri (Iranian Journal of Finance, 1999)
This study was conducted for designing and explaining the convergence-based financial services marketing model in Tehran Stock Exchange. This study was mixed (qualitative-quantitative), and in the qualitative phase, a group of experts in the field of financial services marketing and senior managers of asset management companies were selected and unstructured interview was done for modelling based on ground theory. In the quantitative phase, customers of asset management companies were considered as the statistical population and 500 statistical samples were selected and questioned by questionnaires and 26 hypotheses derived from the initial model were tested. All hypotheses were confirmed but the effect of risk-taking and history of financial services providers on convergence of trends and indexes were rejected. There was also no relationship between history and requirements. Also, conditions and economic fluctuations governing the society and history of financial services providers did not have a significant effect on adherence to requirements of stock exchange.   Finally, the results led to the design of convergence-based financial services marketing model in Tehran Stock Exchange (based on the structure of the paradigm model). Comparing the model of the present study with previous models in the field of financial services marketing, an important and innovative point is the attention of asset manager companies to convergence in the financial markets, which was identified as one of the effective strategies for promoting perceived value and customer loyalty and its effect was also proved. Paying attention to the concept of convergence and contagion between markets and paying attention to parallel markets to get more returns is a significant factor in attracting financial services customers.